Anti-inflammatory effects of SGLT2 inhibitors: focus on macrophages - Rykova, Elena Y.; Klimontov, Vadim V.; Shmakova, Elena; Korbut, Anton I.; Merkulova, Tatyana I.; Kzhyshkowska, Julia (International journal of molecular sciences, 2025)
A growing body of evidence indicates that nonglycemic effects of sodium-glucose cotransporter 2 (SGLT2) inhibitors play an important role in the protective effects of these drugs in diabetes, chronic kidney disease, and heart failure. In recent years, the anti-inflammatory potential of SGLT2 inhibitors has been actively studied. This review summarizes results of clinical and experimental studies on the anti-inflammatory activity of SGLT2 inhibitors, with a special focus on their effects on macrophages, key drivers of metabolic inflammation. In patients with type 2 diabetes, therapy with SGLT2 inhibitors reduces levels of inflammatory mediators. In diabetic and non-diabetic animal models, SGLT2 inhibitors control low-grade inflammation by suppressing inflammatory activation of tissue macrophages, recruitment of monocytes from the bloodstream, and macrophage polarization towards the M1 phenotype. The molecular mechanisms of the effects of SGLT2 inhibitors on macrophages include an attenuation of inflammasome activity and inhibition of the TLR4/NF-κB pathway, as well as modulation of other signaling pathways (AMPK, PI3K/Akt, ERK 1/2-MAPK, and JAKs/STAT). The review discusses the state-of-the-art concepts and prospects of further investigations that are needed to obtain a deeper insight into the mechanisms underlying the effects of SGLT2 inhibitors on the molecular, cellular, and physiological levels.
Gesehen am 17.07.2025